Gambaran Penerapan Terapi Akupresur Pada Lansia Penderita Hipertensi Terhadap Perubahan Tekanan Darah - Dwi Antara Nugraha; Suparmi (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: As time goes by, changes in people's lifestyles, from children to the elderly, are becoming fond of instant foods that contain lots of sodium and fat. Besides that, there is a tendency to be lazy about activities, to carry out monotonous routines which increase the risk of stress. This triggers the emergence of various complaints, one of which is high blood pressure. Objective: This research was conducted by the Elderly Posyandu located in Suren Wetan Canden Jetis Hamlet, Bantul, Yogyakarta. Methodology: The research design in this study is a descriptive quantitative survey. Results: There was a decrease in the average systolic blood pressure of 16.36 mmHg and a decrease in the average diastolic blood pressure of 4.91 mmHg in 11 elderly people who suffered from hypertension. Conclusion: Acupressure therapy was carried out on 11 elderly people who suffered from hypertension at the acupoints GV 20, GB 20, EX-HN 3, EX-HN 5, GB 21, LI 4 and PC 6 by means of massage and rotation which created comfort carried out to the left 30 rounds of each point can reduce the average systole and diastole.